Activation of the AT1R/HIF-1α/ACE Axis Mediates Angiotensin II-Induced VEGF Synthesis in Mesenchymal Stem Cells. (20th October 2014) - Liu, Chao; Zhang, Jing-Wen; Hu, Liang; Song, Yi-Chen; Zhou, Lu; Fan, Yue; Zhu, Hong-Yi; Wang, Yu; Li, Qing-Ping
Abstract : A local renin-angiotensin system (RAS) is expressed in mesenchymal stem cells (MSCs) and regulates stem cell function. The local RAS influences the survival and tissue repairing ability of transplanted stem cells. We have previously reported that angiotensin II (Ang II) pretreatment can significantly increase vascular endothelial growth factor (VEGF) synthesis in MSCs through the ERK1/2 and Akt pathways via the Ang II receptor type 1 (AT1R). However, the role of angiotensin-converting enzyme (ACE) has not been clarified. Furthermore, whether Ang II pretreatment activates hypoxia-inducible factor-1 α (HIF-1 α ) in MSCs has not been elucidated. Our data show that both ACE and HIF-1 α are involved in promoting VEGF expression in MSCs, and that both are upregulated by Ang II stimulation. The upregulation of ACE appeared after the rapid degradation of exogenous Ang II, and led to the formation of endogenous Ang II. On the other hand, the ACE inhibitor, captopril, attenuated Ang II-enhanced HIF-1 α upregulation, while HIF-1 α suppression markedly attenuated ACE expression. This interesting finding suggests an interaction between ACE and HIF-1 α . We conclude that Ang II pretreatment, as a trigger, activated the AT1R/HIF-1 α /ACE axis that then mediated Ang II-induced VEGF synthesis in MSCs.